2008
DOI: 10.1007/s10802-008-9236-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterotyic and Homotypic Continuity: The Moderating Effects of Age and Gender

Abstract: The longitudinal relationships between depression, anxiety, conduct problems, and inattention were investigated. The present study attempted to overcome the methodological limitations of prior research on childhood co-occurring syndromes by using continuous measures of constructs, controlling for multiple symptoms at baseline, and considering the role of age and gender. Using a community sample of 6-11 year-old children, we found evidence of homotypic and heterotypic continuity in baseline characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 57 publications
4
20
0
5
Order By: Relevance
“…However, no differences were noted within the current ADHD sample, comparing participants with and without Lifetime Depression regarding previous and current ADHD severity, age of onset of ADHD and subtype of ADHD. These results echo findings from two studies of ADHD samples (Biederman et al 1998;Blackman et al 2005), but contrast with a study in a clinical sample with ADHD (Connor et al 2003), a study in a clinical sample with ADHD and normal controls (Biederman et al 1996), and studies in community samples enriched with ADHD youth (Herman et al 2007;Reinke and Ostrander 2008). Differences in findings across studies may be related to differences in samples, as most other studies were not exclusively in clinical samples with ADHD.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, no differences were noted within the current ADHD sample, comparing participants with and without Lifetime Depression regarding previous and current ADHD severity, age of onset of ADHD and subtype of ADHD. These results echo findings from two studies of ADHD samples (Biederman et al 1998;Blackman et al 2005), but contrast with a study in a clinical sample with ADHD (Connor et al 2003), a study in a clinical sample with ADHD and normal controls (Biederman et al 1996), and studies in community samples enriched with ADHD youth (Herman et al 2007;Reinke and Ostrander 2008). Differences in findings across studies may be related to differences in samples, as most other studies were not exclusively in clinical samples with ADHD.…”
Section: Discussionsupporting
confidence: 71%
“…Yet, studies regarding the link between the ADHD severity and depression have yielded contradictory findings. Some in community samples have reported an association between depressive and inattentive symptoms (Herman et al 2007;Reinke and Ostrander 2008). Some in clinical samples have noted an association between comorbid depression and general ADHD symptom severity (Biederman et al 1996;Connor et al 2003), while others have found no associations between comorbid depression and ADHD symptom severity (Blackman et al 2005), or ADHD subtypes (Crystal et al 2001;Power et al 2004).…”
Section: Studies Of Non-environmental Correlatesmentioning
confidence: 99%
“…Second, while some attention has been paid to the role that the ODDNA component of ODD may play in subsequent depression (Burke et al, 2010; Burke & Loeber, 2010), and to emotional problems that included symptoms of anxiety and depression jointly (Stringaris & Goodman, 2009a), only one study (Rowe et al, 2010) has examined whether the irritability or the NA dimension of ODD is related to subsequent anxiety. While there is a high level of comorbidity between anxiety and depressive disorders when assessed as categorical constructs, and moderate-to-high correlations between anxiety and depression measured dimensionally (Brady & Kendall, 1992; King, Ollendick, & Gullone, 1991; Seligman & Ollendick, 1998), studies of the latent structure of anxiety and depression suggest that they should be considered to be separate, but correlated constructs (Chorpita, Albano, & Barlow, 1998; Cole, Peeke, Martin, Truglio, & Serczynski, 1998; Cole, Truglio, & Peeke, 1997; Snyder et al, 2009; Strickland et al, 2011). These studies also indicate that the association of different ODD components should be examined separately for both anxiety and depression.…”
Section: Exacerbating/buffering Associations Of Internalizing Symptommentioning
confidence: 99%
“…Results from the few studies using confirmatory factor analysis to examine the latent factor structure of anxiety and depression suggest that viewing them as separate, but correlated, constructs is preferable (Chorpita et al 1998; Cole et al 1997, 1998; Snyder et al 2009; Strickland et al 2011). …”
mentioning
confidence: 99%
“…In a third set of studies (Lewinsohn et al 1995; Reinherz et al 1989; Reinke and Ostrander 2008; Sanford et al 1995) with samples of older children and adolescents, anxiety and depression were examined dimensionally rather than categorically. The categorical approach considers traits or disorders to be dichotomous, (i.e., present or not).…”
mentioning
confidence: 99%